Information Systems and Neuroscience Gmunden Retreat on NeuroIS 2017 (Lecture Notes in Information Systems and Organisation,, 2018)
This book presents the proceedings of the Gmunden Retreat on NeuroIS 2017, reporting on topics at the intersection of Information Systems (IS) research, neurophysiology and the brain sciences. Readers will discover the latest findings from top scholars in the field of NeuroIS, which offer detailed insights on the neurobiology underlying IS behavior, essential methods and tools and their applications for IS, as well as the application of neuroscience and neurophysiological theories to advance IS theory.